Dashboards for improving patient care: Review of the literature - Dowding, Dawn; Randell, Rebecca; Gardner, Peter; Fitzpatrick, Geraldine; Dykes, Patricia; Favela, Jesus; Hamer, Susan; Whitewood-Moores, Zac; Hardiker, Nicholas; Borycki, Elizabeth; Currie, Leanne (International journal of medical informatics (Shannon, Ireland), 2015)
•There is heterogeneity in the setting where dashboards are used.•There is heterogeneity in the design of dashboards and users targeted.•Dashboard use may be associated with improved outcomes in some contexts.•It is unclear what dashboard characteristics are related to improved outcomes. This review aimed to provide a comprehensive overview of the current state of evidence for the use of clinical and quality dashboards in health care environments. A literature search was performed for the dates 1996–2012 on CINAHL, Medline, Embase, Cochrane Library, PsychInfo, Science Direct and ACM Digital Library. A citation search and a hand search of relevant papers were also conducted. One hundred and twenty two full text papers were retrieved of which 11 were included in the review. There was considerable heterogeneity in implementation setting, dashboard users and indicators used. There was evidence that in contexts where dashboards were easily accessible to clinicians (such as in the form of a screen saver) their use was associated with improved care processes and patient outcomes. There is some evidence that implementing clinical and/or quality dashboards that provide immediate access to information for clinicians can improve adherence to quality guidelines and may help improve patient outcomes. However, further high quality detailed research studies need to be conducted to obtain evidence of their efficacy and establish guidelines for their design.